Setting the Agenda in Communication About the COVID-19 Pandemic on Facebook in Viet Nam - Khang Tan Nguyen; Tuong Nguyen Van; Ly Dang Thi Mai; Thu Nguyen Hoang Anh (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
The study utilizes research methods including document analysis, questionnaire surveys, and statistical data processing to examine the reception of information regarding the COVID-19 pandemic during the social distancing period from May 2021 to October 2021 among students of the Faculty of Social Sciences and Humanities, Vietnam National University, Ho Chi Minh City. Through this study, it is observed that the Vietnamese government has directed its efforts towards disseminating information about the COVID-19 pandemic by establishing a public consultation program on the Facebook social media platform, one of the most widely used platforms in Vietnam. Additionally, the study applies the Theory of Agenda-Setting to retrospectively examine how governmental agencies and media outlets have persuaded the public and students regarding COVID-19-related issues during the social distancing period through a well-structured public consultation program.